Population-specific variations in KCNH2 predispose patients to delayed ventricular repolarization upon dihydroartemisinin-piperaquine therapy - Camara, Mahamadou D. (2024)
Funding Information: The study was supported by European and Developing Countries Clinical Trial Partnership (grant number RIA2017T-2018), Medicines for Malaria Venture (Geneva, Switzerland), UK Medical Research Council, Swedish International Development Cooperation Agency, German Ministry for Education and Research, University Claude Bernard (Lyon, France), Malaria Research and Training Centre (Bamako, Mali), Centre National de Recherche et de Formation sur le Paludisme (Burkina Faso), Institut de Recherche en Sciences de la Sant. (Bobo-Dioulasso, Burkina Faso), and Centre National de Formation et de Recherche en Sant. Rurale (Republic of Guinea). In addition, the authors received support from the Swedish Research Council (grant numbers 2019-01837, 2021-02801, 2021-05666, and 2021-06048), the Grants, Innovation and Product Development Unit of the South African Medical Research Council with funds received from Novartis and GSK R&D for Project Africa GRADIENT (grant numbers GSKNVS2/202101/004), the Robert Bosch Foundation, Stuttgart, Germany, and Conselho Nacional de Desenvolvimento Cient\u00EDfico e Tecnol\u00F3gico (CNPq), Brazil (grant number 200075/2022\u20135). T.N.S. is a CNPq Research Productivity Fellow. M.D.C. performed sequencing, analyzed the data, and conducted statistical analyses. Y.Z. conducted computational variant analyses. M.M.T. was involved in the acquisition of drug concentrations. A.D. and S.S. contributed to bioinformatics analyses. N.O. was the cardiologist responsible for cardiac toxicity assessment. A.H.T, M.L.A., B.F., and I.S. oversaw clinical patient recruitment and management. A.A.D. coordinated and oversaw the WANECAM study and critically reviewed the manuscript. P.J.G. and V.M.L designed and supervised the study. M.D.C. and V.M.L. wrote the manuscript. All authors read, reviewed, and approved of the final version of the manuscript. Funding Information: The study was supported by European and Developing Countries Clinical Trial Partnership (grant number RIA2017T-2018), Medicines for Malaria Venture (Geneva, Switzerland), UK Medical Research Council, Swedish International Development Cooperation Agency, German Ministry for Education and Research, University Claude Bernard (Lyon, France), Malaria Research and Training Centre (Bamako, Mali), Centre National de Recherche et de Formation sur le Paludisme (Burkina Faso), Institut de Recherche en Sciences de la Sant. (Bobo-Dioulasso, Burkina Faso), and Centre National de Formation et de Recherche en Sant. Rurale (Republic of Guinea). In addition, the authors received support from the Swedish Research Council (grant numbers 2019-01837, 2021-02801, 2021-05666, and 2021-06048), the Grants, Innovation and Product Development Unit of the South African Medical Research Council with funds received from Novartis and GSK R&D for Project Africa GRADIENT (grant numbers GSKNVS2/202101/004), the Robert Bosch Foundation, Stuttgart, Germany, and Conselho Nacional de Desenvolvimento e Tecnol\u00F3gico (CNPq), Brazil (grant number 200075/2022\u20135). T.N.S. is a CNPq Research Productivity Fellow. Publisher Copyright: Copyright © 2024 Camara et al.